British isles lupus assessment group 2004 index is valid for assessment of disease activity in systemic lupus erythematosus - Chee‐Seng Yee; Vernon T. Farewell; David Isenberg; Anisur Rahman; Lee‐Suan Teh; Bridget Griffiths; Ian N Bruce; Yasmeen Ahmad; Athiveeraramapandian Prabu; Mohammed Akil; Neil McHugh; David D’Cruz; et al. (2007)
Abstract Objective To determine the construct and criterion validity of the British Isles Lupus Assessment Group 2004 (BILAG‐2004) index for assessing disease activity in systemic lupus erythematosus (SLE). Methods Patients with SLE were recruited into a multicenter cross‐sectional study. Data on SLE disease activity (scores on the BILAG‐2004 index, Classic BILAG index, and Systemic Lupus Erythematosus Disease Activity Index 2000 [SLEDAI‐2K]), investigations, and therapy were collected. Overall BILAG‐2004 and overall Classic BILAG scores were determined by the highest score achieved in any of the individual systems in the respective index. Erythrocyte sedimentation rates (ESRs), C3 levels, C4 levels, anti–double‐stranded DNA (anti‐dsDNA) levels, and SLEDAI‐2K scores were used in the analysis of construct validity, and increase in therapy was used as the criterion for active disease in the analysis of criterion validity. Statistical analyses were performed using ordinal logistic regression for construct validity and logistic regression for criterion validity. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results Of the 369 patients with SLE, 92.7% were women, 59.9% were white, 18.4% were Afro‐Caribbean and 18.4% were South Asian. Their mean ± SD age was 41.6 ± 13.2 years and mean disease duration was 8.8 ± 7.7 years. More than 1 assessment was obtained on 88.6% of the patients, and a total of 1,510 assessments were obtained. Increasing overall scores on the BILAG‐2004 index were associated with increasing ESRs, decreasing C3 levels, decreasing C4 levels, elevated anti‐dsDNA levels, and increasing SLEDAI‐2K scores (all P < 0.01). Increase in therapy was observed more frequently in patients with overall BILAG‐2004 scores reflecting higher disease activity. Scores indicating active disease (overall BILAG‐2004 scores of A and B) were significantly associated with increase in therapy (odds ratio [OR] 19.3, P < 0.01). The BILAG‐2004 and Classic BILAG indices had comparable sensitivity, specificity, PPV, and NPV. Conclusion These findings show that the BILAG‐2004 index has construct and criterion validity.